Methods for the economic evaluation of health care programmes - Drummond, Michael F.; Sculpher, Mark J.; Claxton, Karl; Stoddart, Greg L.; Torrance, George W. (Oxford : Oxford University Press, 2015)
The purpose of economic evaluation is to inform decisions intended to improve healthcare. The new edition of Methods for the Economic Evaluation of Health Care Programmes equips the reader with the essential hands-on experience to undertake evaluations, providing a 'tool kit' based on the authors own experience of undertaking economic evaluations.
1. Introduction to economic evaluation -- 1.1. Some basics -- 1.2. Why is economic evaluation important? -- 1.3. The features of economic evaluation -- 1.4. Do all economic evaluations use the same techniques? -- 1.5. Use of economic evaluation in health care decision-making -- 1.6. How to use this book -- 2. Making decisions in health care -- 2.1. Some basics -- 2.2. Informing health care choices -- 2.3. Requirements for economic evaluation -- 2.4. What is the purpose of health care interventions? -- 2.5. Concluding remarks -- 3. Critical assessment of economic evaluation -- 3.1. Some basics -- 3.2. Elements of a sound economic evaluation -- 3.3. Reporting guidelines for economic evaluation -- 3.4. Limitations of economic evaluation techniques -- 3.5. Conclusions -- 3.6. Critical appraisal of published articles -- 4. Principles of economic evaluation -- 4.1. Alternatives, costs, and benefits: some basics -- 4.2. Making decisions about health care -- 4.3. The cost-effectiveness threshold -- 4.4. Making decisions with multiple alternatives -- 4.5. Some methodological implications -- 4.6. Concluding remarks -- 5. Measuring and valuing effects: health gain -- 5.1. Some basics -- 5.2. Using health effects in economic evaluation -- 5.3. Measuring preferences for health states -- 5.4. Methods for measuring preferences -- 5.5. Multi-attribute health status classification systems with preference scores -- 5.6. Mapping between non-preference-based measures of health and generic preference-based measures -- 5.7. Whose values should be used to value health states? -- 5.8. Criticisms of QALYs -- 5.9. Further reading -- 6. Measuring and valuing effects: consumption benefits of health care -- 6.1. Some basics -- 6.2. Assigning money values to the outcomes of health care programmes -- 6.3. What might we mean by willingness to pay (WTP)? -- 6.4. Pragmatic measurement issues in willingness to pay (WTP -- ^ 6.5. Exercise: designing a willingness-to-pay (WTP) survey for a new treatment for ovarian cancer -- 6.6. Other stated preference approaches: discrete choice experiments (DCEs) -- 6.7. Valuation of health effects for health policy decisions -- 6.8. Further reading -- 7. Cost analysis -- 7.1. Some basics -- 7.2. Allowance for differential timing of costs (discounting and the annuitization of capital expenditures) -- 7.3. Productivity changes -- 7.4. Exercise: costing alternative radiotherapy treatments -- 7.5. Concluding remarks -- Annex 7.1 Tutorial on methods of measuring and valuing capital costs -- Annex 7.2 Discount tables -- 8. Using clinical studies as vehicles for economic evaluation -- 8.1. Introduction to vehicles for economic evaluation -- 8.2. Alternative vehicles for economic evaluation -- 8.3. Analytical issues with individual patient data -- 8.4. Conclusions -- 8.5. Exercise -- 9. Economic evaluation using decision-analytic modelling -- 9.1. Some basics -- 9.2. The role of decision-analytic models for economic evaluation -- 9.3. Key elements of decision-analytic modelling -- 9.4. Stages in the development of a decision-analytic model -- 9.5. Critical appraisal of decision-analytic models -- 9.6. Conclusions -- 9.7. Exercise: developing a decision-analytic model -- Annex 9.1 Checklist for assessing quality in decision-analytic models -- 10. Identifying, synthesizing, and analysing evidence for economic evaluation -- 10.1. Introduction to evidence in economic evaluation -- 10.2. Defining relevant evidence -- 10.3. Identifying and reviewing evidence -- 10.4. Synthesizing evidence -- 10.5. Estimating other parameters for economic evaluation -- 10.6. Conclusions -- 10.7. Exercise -- 11. Characterizing, reporting, and interpreting uncertainty -- 11.1. Some basics -- 11.2. Characterizing uncertainty -- 11.3. Is current evidence sufficient? -- 11.4. Implications for approval and research decisions -- 11.5. Uncertainty, heterogeneity, and individualized care -- 11.6. Concluding remarks -- 12. How to take matters further -- 12.1. Taking matters further -- 12.2. Further reading and key sources of literature -- 12.3. Planning and undertaking an economic evaluation -- 12.4. Expanding your network in economic evaluation -- 12.5. Looking to the future.
Includes bibliographical references and index.
Keywords: MEDICAL CARE -- COST EFFECTIVENESS; MEDICAL ECONOMICS; MEDICAL CARE, COST OF EVALUATION